Water transport in plants under climatic stress / M. Borghetti, J. Grace, A. Raschi (edts) - Borghetti, M.; Raschi, A.; Grace, J. (Londres Cambridge University Press, 1993)
The prospect of future climate change has stimulated research into the physiological responses of plants to stress. Water is a key factor controlling the distribution and abundance of plants in nature and the efficient uptake and subsequent transport of water within the plant is critical in hot, dry regions. This book, based on a meeting wich focused on the failure of the hydraulic pathway within the xylem, brings together contributions from a range of experts who have worked on the cavitation of water in the transport system. The phenomenon of cavitation, discovered only in the 1960s, is now becoming recognised as being widespread and, whilst its ecological significance is a matter for further research, many scientists consider that embolism in the xylem predisposes plants to further water stress. Cavitation and refilling may, therefore, hold the key to vegetational responsee to climatic warming and drying. The chapters fall into four sections: the analysis of the mechanism and pathway of water flow in the plant; the natural repair of the hydraulic continuum; the survey of methodologies including acoustic detection of cavitation, thermoelectrical techniques and nuclear magnetic resonance; and, finally, case studies taken mainly from the hot, dry climates of the Souththern Mediterranean. This book will provide a valuable compendium of information for those working in the plant and environmental sciences as well as for those whose interests lie in the more applied disciplines of agriculture and forestry.
Proceeding of an International Workshop, held in Vallombrosa, Firenze, Italy
Keywords: Fisiologia Vegetal; Xilema; Tension de Absorcion; Estres de Sequia; Estres Hidrico; Cavitacion